Human resources and health outcomes: cross-country econometric study - Anand, Sudhir; Bärnighausen, Till (The lancet, 2004)
Background: Only a few studies have investigated the link between human resources for health and health outcomes, and they arrive at different conclusions. We tested the strength and significance of density of human resources for health with improved methods and a new WHO dataset. Methods: We did cross-country multiple regression analyses with maternal mortality rate, infant mortality rate, and under-five mortality rate as dependent variables. Aggregate density of human resources for health was an independent variable in one set of regressions; doctor and nurse densities separately were used in another set. We controlled for the effects of income, female adult literacy, and absolute income poverty. Findings: Density of human resources for health is significant in accounting for maternal mortality rate, infant mortality rate, and under-five mortality rate (with elasticities ranging from -0·474 to -0·212, all p values <0·0036). The elasticities of the three mortality rates with respect to doctor density ranged from -0·386 to -0·174 (all p values <0·0029). Nurse density was not associated except in the maternal mortality rate regression without income poverty (p=0·0443). Interpretation: In addition to other determinants, the density of human resources for health is important in accounting for the variation in rates of maternal mortality, infant mortality, and under-five mortality across countries. The effect of this density in reducing maternal mortality is greater than in reducing child mortality, possibly because qualified medical personnel can better address the illnesses that put mothers at risk. Investment in human resources for health must be considered as part of a strategy to achieve the Millennium Development Goals of improving maternal health and reducing child mortality.